Energy Absorption Characteristics of Frozen Soil Based on SHPB Test - Qin-yong Ma; Dong-dong Ma; Pu Yuan; Zhao-ming Yao (Advances in Materials Science and Engineering)
Dynamic compressive tests are performed in three frozen soil types under different stress states at freezing temperatures of −5°C and −15°C with impact loading pressures from 0.3 MPa to 0.6 MPa. The effects of frozen soil type, freezing temperature, impact loading pressures, and stress states on incident energy and energy absorption characteristics, such as absorbed energy and energy absorbency rate, are investigated. The experimental results show that most of the incident energy is reflected back to the incident bar, and incident energy linearly increases with the increase of impact loading pressures. Both absorbed energy and energy absorbency rate are found to be negatively correlated with freezing temperature, and there values under confining pressure state are larger than that under uniaxial condition. The effects of confining pressure on absorbed energy are quite different at different freezing temperatures. In addition, frozen soil type also affects absorbed energy and energy absorbency rate. Meanwhile, impact loading pressure shows an increased effect on the absorbed energy, but it has little effect on energy absorbency rate in the research.